Feminism and men: Ambivalent space for acting up. (November 2019) - Tienari, Janne; Taylor, Scott
Feminism, historically and today, provides challenges and opportunities to men. In this essay, we present a dialogue that highlights different positions on men's activism and thought in relation to feminism. We argue that it is essential for men to engage with feminism as activists and in theory, although this may present risks subjectively, professionally and interpersonally. To illustrate our argument, we provide examples of engagement and distance from our working lives in different socio-cultural contexts. We explore questions of vulnerability and uncertainty in learning from feminism, and discuss how our privileges as (White, middle-aged, permanently employed) men condition our ambivalent experiences. The essay is oriented towards encouraging ourselves/men to articulate what feminism in action means, through research, teaching and professional identity work. We consider throughout the conditions of possibility for men in acting up with feminism in critical organization and management studies, in the hope that practical action can create better conditions of work for all of us.